ANALISIS PENGARUH JUMLAH PENDUDUK YANG BEKERJA DAN INVESTASI TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN MELALUI PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI BALI - Adipuryanti, Ni Luh Putu Yuni; Sudibia, I Ketut (PIRAMIDA; Vol 11 No 1 (2015): Jurnal PIRAMIDA, 2015)
The difference in economic growth between regions would lead to unequal distribution of income. Unequal distribution of income can be caused by several factors, including uneven amount of labor and investment in an area. The purpose of this study was to analyze the effect of directly or indirectly the working population and the investment of the unequal distribution of income through economic growth in the district/city in the province of Bali. This research uses secondary data from 2007-2013. This study uses data collecting non-participant observation. The analysis technique used is path analysis. Based on the analysis found that the number of people who work and investment positive and significant impact on economic growth. Economic growth is positive and significant effect on the unequal distribution of income. Meanwhile, the number of people working and investing no significant effect on inequality of income distribution. Economic growth is a variable mediating the indirect influence of the working population and the investment of the unequal distribution of income.
Keywords: inequality of income distribution, the number of working population, investment, economic growth